Integrating smart contracts with Islamic economic law: A Sharia design framework for digital finance governance - Hasanuddin, Hasanuddin; Malik, Abdul; Tuo, Hana (Journal of Islamic Economics Lariba, 2026)
IntroductionSmart contracts have become an important innovation in blockchain-based digital transactions because they enable automated, transparent, immutable, and self-executing agreements. In Islamic economic law, however, contracts are not merely technical instruments but also ethical and legal commitments that must fulfill the principles of consent, clarity, justice, lawful subject matter, and freedom from prohibited elements such as usury, excessive uncertainty, and gambling. This creates an important scholarly issue concerning whether smart contracts can be integrated with sharia contract principles in the digital age.ObjectivesThis study analyzes the compatibility of smart contracts with Islamic economic law and examines their legal and regulatory position in Indonesia. It also formulates an Islamic Smart Contract Framework as a conceptual model for integrating blockchain technology with sharia contract validation, digital sharia supervision, and legally accountable execution.MethodThis study uses a normative-juridical approach based on secondary legal and scholarly materials. The analysis examines Indonesian regulations on electronic contracts, personal data protection, Islamic banking, and financial technology, along with fatwas issued by the National Sharia Council of the Indonesian Ulema Council. Academic literature on blockchain, smart contracts, Islamic contract theory, sharia fintech, and comparative practices in Malaysia, Bahrain, and the United Arab Emirates is also reviewed. The data are analyzed descriptively, normatively, comparatively, and conceptually.ResultsThe findings show that smart contracts can support Islamic economic transactions when they function as technical instruments for executing valid sharia contracts. They can strengthen transparency, legal certainty, transaction efficiency, auditability, and trust. However, smart contracts cannot independently ensure contractual intent, consent, legal capacity, fairness, public benefit, or compliance with the higher objectives of sharia. Their implementation therefore requires sharia contract validation, fatwa-based supervision, digital sharia audits, hybrid dispute resolution, and clear regulatory standards.ImplicationsThis study provides a conceptual basis for regulators, sharia authorities, Islamic financial institutions, and fintech developers to design smart contracts that are technologically reliable, legally recognized, and sharia-compliant.Originality/NoveltyThis study contributes by proposing the Islamic Smart Contract Framework as a sharia-by-design model that integrates contract validation, programmable code structure, algorithmic sharia auditing, and blockchain-based execution.